The Development of Character-Based Assessment Instruments in Poetry Writing Material for Class X Students of SMA Negeri 3 Medan - Muhammad Sadri; Abdurahman Adisaputera; Syahnan Daulay (BIRCU, 2020)
Early observations made on the Indonesian language teacher, Henny Indriany, S.Pd. at SMAN 3 Medan, explained that the assessment instrument carried out by the teacher was only on the selected assessment technique according to the characteristics or abilities of students. Whereas the assessment process in writing scientific papers is very good and effective if the principles of this assessment are considered when the teacher is: (1) there are clear restrictions on what is prioritized for assessment. (2) the selected assessment technique must be in accordance with the characteristics or abilities to be measured. (3) comprehensive assessment requires various types of assessment techniques. (4) should be aware that the assessment techniques used have limitations. (5) the assessment must be used to improve the learning achievement of students. Data regarding the quality of the character assessment instrument based on rational data (validator assessment) is taken using a validation sheet filled in by experts in the field of educational assessment, and the preparation of a psychological scale. The expert validation sheet consists of four answer scores, namely 1, 2, 3, and 4. The number of questions is 20 items so that the range of scores obtained is between 20-80. The results obtained are converted into the following eligibility criteria. Learning Indonesian, especially writing poetry based on character education which is served to students, aims to train students to be skilled in language, especially writing by expressing ideas and feelings creatively and critically. Learning to write poetry in high school according to the 2013 Curriculum aims to improve the skills of students in appropriate and creative language, increase the ability to think logically, critically and reason, and increase the sensitivity of feelings and the ability of students to understand and implement the values of character education in everyday life. day and in the school environment.